A regra matriz de incidência do Imposto sobre a Propriedade de Veículos Automotores - IPVA - Bernini, Cassiano Inserra (2010)
This work constructs the source rule for the Tax on Property of Automotive Vehicles (IPVA) levy. The competence to establish and collect this tax was given to the States and the Federal District by article 155, item III, of the 1988 Federal Constitution of Brazil. The methodology conceived by the Logical and Semantic Constructivism was used to study the theme. According to said methodology, the Law is taken as a cultural object expressed in language and based on the categories of the Philosophy of Language. Initially, the object is submitted to an analytical analysis and following it is reconstructed with emphasis on the syntactic, semantic and pragmatic aspects of the terms. The work starts with some brief considerations on the legal rule and the source rule for the tax levy. Following, the work focuses on the historical aspects involving the IPVA and the possible requirement for the prior enactment of a nationwide supplementary law providing for the elements of the source rule for this tax levy enabling the competent political entities to establish it. This work also addresses the constitutional principles applicable to the IPVA. Finally, the source rule for the IPVA levy is constructed through a detailed analysis of all its constituent criteria